Augmented Reality Application for Human Five Senses Recognition - Ilham Wisnu Bachtiar; Cindy Taurusta; Azmuri Wahyu Azinar (SMATIKA JURNAL : STIKI Informatika Jurnal, 2025)
This study aims to design a maekerless Augmented Reality based application as a interactive learning media for the introduction of the five human senses for elementary school students. This application uses the Multimedia Development Life Cycle (MDLC) method because it is in accordance with the manufacturing stage. Features in This application displays 3D visualization of the organs of the five senses that can be manipulated by the user, complete with additional information in the form of text and audio. Feasibility testing conducted on elementary school students and teacher showed that the app had an excellent succes rate, with an average score of 98,1% based on a Likert Scale. This result shows that the application succesfully increasses student interest and effectively improves students understanding of the aterial of the five senses.